PENGARUH IMPLEMENTASI GOOD CORPORATE GOVERNANCE, PENGENDALIAN INTERN KAS, ASIMETRI INFORMASI TERHADAP FRAUD (Studi Pada BUMN Kota Pekanbaru) - Oktariani Wefa; Nurazlina '; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study examined the effect of the Implementation of Good Corporate Governance, The Internal Control of Cash, The Information Asymmetry of Fraud (Empirical Study On Government BUMN Pekanbaru City). Data that is used in this research is primary data, that was collected by survey techniques by distributing questionnaires to each functionary at BUMN in Pekanbaru. The population is BUMN company in Pekanbaru many as 33 companies. The selection of sample used purposive sampling method. The sample was (total) the respondent of each corporate represented by three respondents, head branch, head division, and accounting staff. A questionnaire distributed to 99 respondents, and successfully reassembled with complete answers are obtained from 66 respondents. The result of the study showed that the implementation of good corporate governance, the internal control of cash, and information asymmetry has significant effect and positively effects cheating of fraud. Determinate Coeffisience show the result that Adjusted R Square value as 0,806. It means that the effect of Implementation of Good Governance, The Cash Intern Control, Information Asymmetry on Fraud as many as 80,6%. While other 19,4 % will be explained by other variable which was not included in the study.Keywords: Governance, Cash Control, Information Asymmetry, and Fraud